The Relative Pricing of High-Yield Debt: The Case of RJR Nabisco Holdings Capital Corporation - Dammon, Robert M.; Dunn, Kenneth B.; Spatt, Chester S. (American Economic Review, 1993)
We derive and investigate empirically arbitrage pricing restrictions among three bonds of RJR Nabisco Holdings Capital Corporation. The three RJR bonds are virtually identical in all respects, except for the form in which interest is paid. We document large and persistent errors in the market pricing of the three bonds over a two-year period. The cash-paying bond was consistently more expensive than either the pay-in-kind or deferred-coupon bonds. The magnitude of the pricing errors is too large to be explained by market imperfections.